(3GdJbhje GdPGJj aj GdJQHjIs - (3Ndjd, eMeO GdMGLs ((3HjQhJs (3GdeDSSI GdYQHjI ddOQGSGJs, 2006)
(3jbUO HGdJbhje GdPGJj Cf jbhe GdGfSGf PGJg HPGJg, ajMGSH faSg hjQGLYgG GdMSGH, Ke jJUQa aj VhA gPG GdMSGH(B. (3aEeG Cf jYJR HeeGQSGJg hjYRRgG Ch jYOdgG hjWhQgG(B. (3gPG hEf acQI Cf jbhe GdEfSGf PGJg acQI bOjeI bOe GdEfSGf(B. (3agh, dh cGf jYed Ydi eMGSHI faSg ERGA eG jYedg, hYdi eQGLYI eeGQSGJg HYO EJjGfgG(B. (3hGdKbGaI GdYQHjI hGdJQGK GdESdGej MGadGf HOYhI GdaQO Edi Jbhje faSg heMGSHI PGJg(B. (3agh GdHUjQ HfaSg hOhGaYg hSdhcg hJUQaGJg hGdYGQa Hejhdg heTGYQg hGJLGgGJg(B. (3hgh GdeObb hGdeMGSH GdChd dPGJg aj cd eG jeGQSg(B. (3hacQI GdJbhje GdPGJj aj GdJQHjI GdeYGUQI dG JYOh eG JbOe(B. (3agj YedjI Cf jMGSH GdYGed GdJQHhj PGJg hjbhe eeGQSGJg aj eLGd eYjf, hab eYGjjQ Ch CHYGO Ydi gjFI fbGW Ch HfhO, JJVefgG UMjaI Jbhje PGJj NGUI HPdc GdeLGd, dcf GdeCdha MJi GdBf Cf jJe Jbhje GdYGed GdJQHhj ef bHd eQGbHjf Ch RGFQjf jahbhfg eYQaI hNHQI, hjJbOehf Ydjg aj ehGbY GdeSDhdjI hGdSdWI(B. (3CeG GdJbhje GdPGJj ddYGed GdJQHhj agh GdJbhje GdPj jbhe Hg GdYGed GdJQHhj PGJg, aj eYRd Yf eQGbHjf ef GdNGQL, ef NdGd COGI Jchf aj eJfGhd jOg JSei (B"(3UMjaI Jbhje PGJj (B". (3hgcPG aEf GdJbhje GdPGJj, EVGaI Edi GdYGed GdJQHhj agh aj Pdc hSjdI hZGjI, hdG JbJUQ YedjI GdJbhje GdPGJj Ydi GdYGed GdJQHhj, ShGA CcGf eYdekG Ce eOjQkG, eTQakG JQHhjkG Ce NHjQkG, Pdc Cf GdEfSGf cGFfkG eG cGf Yedg, jLQj gPg GdYedjI GdJbhjejI Ydi Tcd eQGLYI PGJjI deG bGe Hg(B. (3hjJHjf hMOg ehGVY fLGMg ajYJR HgG hehGbY ENaGbg ajYed Ydi JMGTjgG Ch JYOjdgG(B. (3gPG hEf GdJbhje GdPGJj Gdjhe jeKd MQcI JQHhjI eYGUQI JSJMb GdJhVjM hGdGgJeGe(B. (3heY Cf HYV HQGeL JQHjI GdeYdejf Ydi GdeSJhjjf GdYQHj hGdOhdj, JSJNOe HYV COhGJ GdJbhje GdPGJj, EdG Cf GdCSGS GdfXQj dgPg GdMQcI de jdb GdGgJeGe GdcGaj(B. (3heG GdOdjd GdeWQhM aj gPG GdcJGH EdG eMGhdI dJWhjQ MQcI GdJbhje GdPGJj hJYRjR JhXjagG, HhUa gPG GdfhY ef GdJbhje hSjWI JOQjHjI JJcGed eY ZjQgG ef hSGFW GdJOQjH aj GdefMi GdJcGedj GdeJYOO GdhSGFW(B. (3hdPdc aEf gPG GdOdjd jYed Ydi JYRjR GdEWGQjf GdfXQj hGdJWHjbj, HeG jTJed Ydjg ef fXQjI hJWHjbGJ eJeKdI aj GdCOhGJ GdJj jecf GSJNOGegG ejOGfjkG, aJSge aj JYRjR GdJQHjI GdeSJOGeI ddeQHj(B. (3hJHdZ gPg GdCOhGJ JSY YTQI UMjaI Jbhje PGJj(B. (3hCNjQkG jecf Gdbhd HCf GdJbhje GdPGJj dG jYOh aj GdJQHjI GdeYGUQI eG JbOe, agh EVGaI Edi chfg fhYkG ef GdJbhje GdJQHhj gh jYO ZGjI HMO PGJg jDed Cf jUd EdjgG GdYGed GdJQHhj , agh aj Pdc hSjdI hZGjI(B.s
(3GdfhY (B: (3cJGHs
Keywords: Evaluation Scolaire; School Evaluation; (3GdJbjje GdeOQSjs